Physical Separation and Hydrometallurgical Processes for Treatment of Weee - H. Deveci1; E. Y. Yazici1; A. Akcil; C. Erust; O. Celep (International Mineral Processing Congress, 2018)
"Recycling of WEEE has already gain prime importance from both environmental and economic point of view. For the recovery of metals from e-waste, many conventional physical, bio/hydrometallurgical and pyrometallurgical processes are proposed. Economic potential of e-waste is mainly driven by its precious metal content. Physical separation methods (e.g. electrostatic, magnetic, eddy current and gravity separation) exploit the differences in the physical properties of metals and non-metals. Physical separation methods are simple and economically sound but they suffer from metal losses and ineffectiveness at fine sizes. Hydrometallurgical processes are promising owing to their relatively low cost, reduced environmental impact, potential for high metal recoveries and suitability for small scale applications. Hydrometallurgical processes can be developed for selective extraction of base/precious metals using suitable reagent systems. Sulphate-based leaching with a suitable oxidant (e.g. H2O2, O2, Fe3+) is effective for copper and other base metals. After removal/recovery of base metals, precious metals can be easily extracted using various lixiviants including thiosulphate, thiourea, cyanide and chloride. However, further research is required to develop new, cost effective and environmentally friendly processes and/or refine existing ones for leaching and, in particular, downstream processes. INTRODUCTION Electrical and electronic equipments are indispensable to modern societies with numerous applications in the field of medicine, transport, communication, education, security and environmental protection. With technological developments and innovations, the replacement of old equipment leads to ever fast accumulation of waste materials such as waste electrical and electronic equipment (WEEE or e-waste). People are upgrading their mobile phones, computers, televisions, audio equipment and printers more frequently than ever before (Babu et al., 2007; Lee et al., 2007). With the rapid growth in technology today, the life span and utilisation period of most electronic and electrical equipment has been reduced considerably with concomitant generation of huge amounts of WEEE over the past several decades. According to statistics presented by Balde et al. (2015), total WEEE produced around the world was 41.8 million tonnes in 2014 and expected to rise to approximately 50 million tonnes by 2018. Kumar et al. (2017) estimated that annual growth rate for the WEEE stream is 3–5% (Singh et al., 2016). The aim of this paper is to provide an overview of physical separation and hydrometallurgical methods available for the treatment of WEEE."